Enzyme-responsive cell-penetrating peptides conjugated mesoporous silica quantum dots nanocarriers for controlled release of nucleus-targeted drug molecules and real-time intracellular fluorescence imaging of tumor cells - Costa, Marianne (2014)
Here, a set of novel and personalized nanocarriers are presented for controlled nucleus-targeted antitumor drug delivery and real-time imaging of intracellular drug molecule trafficking by integrating an enzyme activatable cell penetrating peptide (CPP) with mesoporous silica coated quantum dots nanoparticles. Upon loading of antitumor drug, doxorubicin (DOX) and further exposure to proteases in tumor cell environment, the enzymatic cleavage of peptide sequence activates oligocationic TAT residues on the QDs@mSiO2 surface and direct the DOX delivery into cellular nucleus. The systematic cell imaging and cytotoxicity studies confirm that the enzyme responsive DOX-loaded CPP-QDs@mSiO2 nanoparticles can selectively release DOX in the tumor cells with high cathepsin B enzyme expression and greatly facilitate DOX accumulation in targeted nucleus, thus exhibiting enhanced antitumor activity in these cells. As contrast, there is limited nuclear-targeted drug accumulation and lower tumor cytotoxicity observed in the cells without enzyme expression. More importantly, significant antitumor DOX accumulation and higher tumor inactivation is also found in the drug resistant tumor cells with targeted enzyme expression. Such simple and specific enzyme responsive mesoporous silica-QDs nanoconjugates provide great promise for rational design of targeted drug delivery into biological system, and may thus greatly facilitate the medical theranostics in the near future.